How can Christian love be taught using the ‘spiritual cinema’? - Baranova, Jūratė (Acta Universitatis Nicolai Copernici Pedagogika, 2020)
The article reflects upon one aspect of multimodal education – the possibility to teach moral matters with films. This possibility was discerned by American film philosopher Stanley Cavell. It was also discussed in detail by American social science teacher W.B.Russell III, The author of this particular article sees some essential similarities and some differences between Russell’s suggested methodologies and stages and the methodology she developed herself and started to use actively from 2002 teaching practical philosophy in some Lithuanian universities in practical philosophy courses. She is using films as an analogy. Educators using this method of teaching with films customarily stress its purpose as being to develop critical-thinking ability and acquire knowledge. But is it possible to use cinema in education for acquiring sensitivity to certain values? For example, the ability to recognize the values of Christian ethics? The article discusses the results of multimodal teaching experiment teaching Christian ethics with two feature films: Ingmar Bergman’s The Winter Light (1963) and Robert Bresson’s Diary of a Country Priest (1951). As the results of teaching experiments were reflected the values of suffering, love and patience discerned by the students.